Causal factors of project success affecting the business growth of residential real estate - Punya, Yutthasart; U-on, Vichit (Edelweiss Applied Science and Technology, 2025)
Real estate is one of the fastest-growing and rapidly evolving industries. In Thailand, the real estate industry has seen remarkable development across all categories, including residential properties, commercial buildings, and condominiums. However, this industry continues to face several challenges that affect its long-term growth and sustainable development. Key issues, their causes, and potential solutions in the residential real estate sector include rising prices, limited access to financing, economic risks, market oversupply, regulatory and legal constraints, market uncertainty, and property management problems. The objectives of this research are: 1) to examine the causal factors affecting the project success and business growth of residential real estate, 2) to analyze the influence of causal factors of project success affecting the growth and profitability of residential real estate, and 3) to develop a causal model of project success factors affecting the growth and profitability of residential real estate. The researcher collected data through interviews and online questionnaires targeting residential real estate between March and April 2025, with a sample size of 400 respondents. The analysis results indicate that leadership affects project success, leadership affects business growth through project success, risk management affects project success, risk management affects business growth through project success, and project success affects business growth. Entrepreneurs can make better decisions regarding business expansion or investment in new projects and can manage various situations more effectively, thereby gaining a competitive advantage and achieving their business goals as planned.